(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
To get Schiff bases derivatives malonic acid di hydrazide was reacted with CS2 KOH, followedby hydrazine hydrate. This produced 1,2,4-triazole, which was then reacted with various substitutedbenzaldehydes. Thiazolidines were produced via the reaction of Schiff bases with thioglycolic acid. Asimilar reaction between Schiff bases and glycine yielded imidazolidinone. FT-IR, 1 H-NMR, Uvvis spectra,melting temperatures, and T.L.C. purity checks were used to describe the compounds. Antibacterialactivity was tested on a subset of the produced compounds.